Konsep pengembangan gallery, library, archive, dan museum (GLAM) Keanekaragaman Hayati di kawasan Cibinong Science Center - Maha, Rahmadani Ningsih; Wulan, Sri (Daluang: Journal of Library and Information Science, 2022)
Background. Gallery, Library, Archive, and Museum (GLAM) for biodiversity is a documentation center for research institutions on biodiversity as a means of transferring information and knowledge to the public. The functions of education, research, preservation, information, and recreation can be obtained from GLAM. The goal of this study is to inform the potential and form of GLAM innovation in the Cibinong area so that it can become a National Documentation Center for Biodiversity.Methods. The research method uses the observation method by looking at facts in the field and literature studies to support this research.Results and discussion. This study describes the Cibinong Science Center area has five libraries of various disciplines. Regarding biodiversity, the Cibinong area has a biology library with a collection of more than 10,000 books. In the zoology building, there is an animal biodiversity gallery located under the library building. In addition, the Research Center for Biology has a collection of animal specimens in the zoology building, a collection of herbarium specimens at the Botanical Building and the InaCC Building (Indonesian Culture Collection) to store microorganisms.Conclusions. The concept of developing GLAM for Biodiversity in Cibinong Science Center can be applied. Collaboration with other documentary unit manager such archivist and specimen curators must be carried out in order to create GLAM for Biodiversity. The concept of innovation in the development of GLAM is to integrate it in one building and management.